Development of antifouling poly(vinyl chloride) blend membranes by atom transfer radical polymerization. Issue 6 (11th October 2017) - Fang, Li‐Feng; Matsuyama, Hideto; Zhu, Bao‐Ku; Zhao, Shuaifei
ABSTRACT: In this study, antifouling poly(vinyl chloride) (PVC) blend membranes were prepared by blending the PVC based amphiphilic copolymer PVC ‐g‐ poly(hydroxyethyl methacrylate) (PVC‐ g ‐PHEMA), synthesized by atom transfer radical polymerization (ATRP), into the hydrophobic PVC matrix via the nonsolvent‐induced phase separation method. The in situ ATRP reaction solutions were also used as the blend additives to improve membrane performance. Attenuated total reflectance–Fourier transform infrared spectroscopy and X‐ray photoelectron spectroscopy indicated that the blend membranes based on the two blend routes exhibited similar surface chemical compositions. The membrane morphology and surface wettability were determined by scanning electronic microscopy and water contact angle measurement, respectively. The blend membranes showed improved water permeability, comparable rejections and enhanced antifouling properties compared with the pure PVC membrane. The PVC blend membranes also had excellent long‐term stability in terms of chemical compositions and fouling resistance. The results demonstrated that ATRP was a promising technique to synthesize amphiphilic copolymer and prepare stable blend antifouling membranes. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45832. Abstract :